Dose-dependent changes in renal 1H-/23Na MRI after adjuvant radiochemotherapy for gastric cancer = Dosisabhängige Veränderungen im 1H-/23Na-MRT der Niere nach adjuvanter Radiochemotherapie beim Magenkarzinom - Haneder, Stefan; Budjan, Johannes; Schönberg, Stefan; Schad, Lothar R.; Hofheinz, Ralf-Dieter; Wenz, Frederik; Boda-Heggemann, Judit (Strahlentherapie und Onkologie, 2014)
Purpose: Combined radiochemotherapy (RCT) for gastric cancer with three-dimensional conformal radiotherapy (3D-CRT) results in ablative doses to the upper left kidney, while image-guided intensity-modulated radiotherapy (IG-IMRT) allows kidney sparing despite improved target coverage. Renal function in long-term gastric cancer survivors was evaluated with 3T functional magnetic resonance imaging (MRI) including diffusion-weighted imaging (DWI) and 23Na imaging. Patients and methods: Five healthy volunteers and 13 patients after radiotherapy were included: 11×IG-IMRT; 1×3D-CRT; 1× “positive control” with stereotactic body radiotherapy (SBRT) of a metastasis between the spleen/left kidney. Radiation doses were documented for the upper/middle/lower kidney subvolumes. Late toxicity was evaluated based on CTC criteria, questionnaire, and creatinine values. Morphological sequences, DWI images, and 23Na images were acquired using a 1H/23Na-tuned body-coil before/after intravenous water load (WL). Statistics for [23Na] (concentration) and apparent diffusion coefficient (ADC) values were calculated for upper/middle/lower renal subvolumes. Corticomedullary [23Na] gradients and [23Na] differences after WL were determined. Results: No major morphological alteration was detected in any patient. Minor scars were observed in the cranial subvolume of the left kidney of the 3D-CRT and the whole kidney of the control SBRT patient. All participants presented a corticomedullary [23Na] gradient. After WL, a significant physiological [23Na] gradient decrease (p < 0.001) was observed in all HV and IG-IMRT patients. In the cranial left kidney of the 3D-CRT patient and the positive control SBRT patient, the decrease was nonsignificant (p = 0.01, p = 0.02). ADC values were altered nonsignificantly in all renal subvolumes (all participants). Renal subvolumes with doses ≥ 35 Gy showed a reduced change of the [23Na] gradient after WL (p = 0.043). No participants showed clinical renal impairment. Conclusions: Functional parameters of renal 23Na MRI after gastric IG-IMRT are identical to those of healthy volunteers, in contrast to renal subvolumes after ablative doses in the control and 3D-CRT patient. While kidney doses to the cortex below 20-25 Gy in fractional doses of ~ 1 Gy in IG-IMRT (combined with intensified chemotherapy) do not seem to cause significant MRI morphological or functional alterations, doses of > 35 Gy in 1.5-2 Gy fractions clearly result in impairment.